Emergency department care experiences among people who use substances: a qualitative study - Dana Rajab; Jamie K. Fujioka; Melanie Walker; Susan A. Bartels; Meredith MacKenzie; Eva Purkey (International Journal for Equity in Health, 2023)
Abstract Background People who use substances (PWUS) encounter significant barriers to accessing care for their complex health needs. As a result, emergency departments (EDs) often become the first point of healthcare access for many PWUS and are a crucial setting for the study of health inequities. This study aimed to understand the ED healthcare experiences of PWUS with the intent of informing ways of improving the delivery of equitable care. Methods This qualitative study was part of a larger cross-sectional, mixed-methods study that examined ED experiences among diverse underserved and equity-deserving groups (EDGs) within Kingston, Ontario, Canada. Participants shared and self-interpreted a story about a memorable ED or UCC visit within the preceding 24 months. Data from participants who self-identified as having substance use experiences was analyzed through inductive thematic analysis. Results Of the 1973 unique participants who completed the survey, 246 participants self-identified as PWUS and were included in the analysis. Most participants were < 45 years of age (61%), male (53%), and white/European (57%). 45% identified as a person with a disability and 39% frequently struggled to make ends meet. Themes were determined at the patient, provider, and system levels. Patient: history of substance use and experience of intersectionality negatively influenced participants’ anticipation and perception of care. Provider: negative experiences were linked to assumption making, feelings of stigma and discrimination, and negative perceptions of provider care. Whereas positive experiences were linked to positive perceptions of provider care. System: timeliness of care and the perception of inadequate mental health resources negatively impacted participants’ care experience. Overall, these themes shaped participants’ trust of ED staff, their desire to seek care, and their perception of the care quality received. Conclusions PWUS face significant challenges when seeking care in the ED. Given that EDs are a main site of healthcare utilization, there is an urgent need to better support staff in the ED to improve care experiences among PWUS. Based on the findings, three recommendations are proposed: (1) Integration of an equity-oriented approach into the ED, (2) Widespread training on substance use, and (3) Investment in expert resources and services to support PWUS.